The way we eat now : how the food revolution has transformed our lives, our bodies, and our world - Wilson, Bee (Basic Books, 2019)
Food is one of life's great joys. So why has eating become such a source of anxiety and confusion? Bee Wilson shows that in two generations the world has undergone a massive shift from traditional, limited diets to more globalized ways of eating, from bubble tea to quinoa, from Soylent to meal kits. Paradoxically, our diets are getting healthier and less healthy at the same time. For some, there has never been a happier food era than today: a time of unusual herbs, farmers' markets, and internet recipe swaps. Yet modern food also kills--diabetes and heart disease are on the rise everywhere on earth. This is a book about the good, the terrible, and the avocado toast. A riveting exploration of the hidden forces behind what we eat, The Way We Eat Now explains how this food revolution has transformed our bodies, our social lives, and the world we live in.